PENGARUH STRES KERJA, KOMITMEN ORGANISASIONAL, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Monica, Tiya Jumani; Putra, Made Surya (E-Jurnal Manajemen; Vol 6 No 3 (2017), 2017)
This study aims to 1) determine the effect of work stress on turnover intention, 2) the effect of organizational commitment to turnover intention, and 3) the effect of job satisfaction on turnover intention. The study was conducted at two hotels in the village of Mas, District of Ubud, Gianyar, Bali, Taman Harum and Hotel Bali Spirit. The number of respondents in this study as many as 83 people. Collecting data by questionnaires that use 5-point Likert scale to measure 30 indicators. The data analysis technique is a multiple linear regression analysis. Research shows that job stress positive effect on turnover intention. The results obtained subsequent ie, organizational commitment negatively affect turnover intention. Research also get the results that job satisfaction negatively affect turnover intention.
Keywords: job stress, organizational commitment, job satisfaction, turnover intention